Imbal Hasil Sukuk dalam Perspektif Syariah: Analisis pada Sukuk Ritel Indonesia - Aina Izzati Zuhria; Sulistiyah Sulistiyah; Ahmad Ibnul Karim; M. Aqim Adlan; Dede Nurrohman (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to analyze the return mechanism of Indonesian Retail Sukuk and evaluate its conformity with Islamic principles. The research employs a qualitative approach using a literature review method by examining academic journals, official government documents, and regulations related to sukuk. The findings indicate that retail sukuk utilizes an ijarah contract with underlying assets in the form of state-owned assets or government projects. The return received by investors is derived from ujrah (rental income) generated from the utilization of these assets, distinguishing it conceptually from interest-based returns in conventional bonds. The existence of underlying assets enhances transparency and ensures compliance with Sharia principles by avoiding elements of riba, gharar, and maysir. However, the fixed-return characteristic of retail sukuk continues to generate discussion regarding its substantive compliance with Islamic principles. This study concludes that retail sukuk formally complies with Sharia requirements through asset-backed structures and valid contracts, although further research is needed to assess its substantive implementation in modern Islamic finance practices.